LIMB SPLINTING FOR INTRAVENOUS CANNULAE IN NEONATES AND ITS EFFECTS ON LIFE SPAN OF INTRAVENOUS CANNULAE (Journal of Medical & Health Sciences Review, 2025)
Background: Peripheral intravenous (IV) cannulation is essential for administering medications in neonates but often has a short lifespan, leading to repeated procedures and increased risk of complications. The effectiveness of limb splinting in extending the dwell time of IV cannulae remains to be debated, with inconsistent findings reported in the literature. This study aimed to evaluate the impact of limb splinting on the lifespan of IV cannulae in neonates and to compare the incidence of associated.Methods: A randomized controlled trial was conducted. A total of 248 cannulations were randomized into two groups: 123 received IV cannulation with limb splinting and 125 without splinting. The primary outcome was the dwell time of the IV cannula, measured from insertion to removal. Secondary outcomes included the frequency of complications such as extravasation, accidental dislodgment, and leakage. Data were analyzed using SPSS version 26, with statistical significance at p